Salmine and the homeotic integrity of early embryos of Norway spruce - Don J. Durzan (Цитология и генетика, 2010)
Salmine, an arginine-rich protamine, is explored for its concentration-dependent potential to restructure the genome and remodel the homeotic development of Norway spruce embryos expressing monozygotic cleavage polyembryony (MCP). In controls and at low salmine, two protein fractions on SDS-PAGE gels were associated with cells responsible for generating the basal plan for early embryogenesis. With high salmine, embryonal initials no longer differentiated into embryonal tubes. Embryos having embryonal tubes no longer enucleated and differentiated into embryonal suspensors. Biomass and amino acid N declined. Nuclear and cytoplasmic organization was disrupted and nucleoli were highly vacuolated. The transcription of the two protein fractions, PCNA (cyclin) activity and MCP were blocked. Cellular proteins were turned over by proteasomal ubiquitination and others released into the culture medium. Biomass loss and gluconeogenesis of amino acids led to the accumulation of free arginine N. No evidence was obtained with salmine for the remodeling of cells into gametes.